Internationalisation and performance in Spanish family SMES: The W-curve - Marta Fernández Olmos; Ana Gargallo-Castel; Enrique Giner Bagüés (BRQ Business Research Quarterly, 2016)
Summary Previous studies have provided mixed evidence on the relationship between internationalisation and firm performance. We advance theoretically in this line of research by investigating the impact of the family dimension of a business on this relationship. Using a panel data analysis for the 2006–2011 period, we find empirically that Spanish family SMEs follow a W-curve. Our findings highlight the importance of differentiating family from non-family firms, and provide a potential explanation for the previous mixed evidence."
Keywords: 650; Family firm; Internationalisation; Firm performance; W-curve